The challenges that are facing the assest management unit in the Limpopo Department of Economic Development, Environment and Tourism (LEDET), South Africa - Ramosebudi, Sewela Magreth (My University, 2015)
The Department of Economic Development, Environment and Tourism is mandated to focus on growing the provincial economy, empowering women and youth, on supporting small businesses and co-operatives and improving the lives of the people of the province for the better as indicated in the Limpopo Economic Development, Environment and Tourism Province Budget Vote (2015/16). Economic growth and social wellbeing are closely tied to the ability to protect the natural environment. Mining, electricity generation and agriculture are among the economic activities that have a direct impact on the environment and need to be carried out in a sustainable and responsible manner. Towards this vision, the assets which are furniture, transport, computer hardware and other machinery and equipment need to be managed efficiently and effectively in order to fulfil the needs of society and the departments. These assets represent an enormous value for the owner which is LEDET and for society at large. To grasp the full potential of these assets, a deep and thorough understanding of an asset’s complete lifetime is needed. However, the assets especially physical assets, public buildings and infrastructures are not managed properly and that results in numerous challenges and audit queries that are raised by the Auditor General. The purpose of this study was to investigate the challenges that are facing the asset management unit of Limpopo Department of Economic Development & Tourism (LEDET). Asset Management has been hailed as important in order to enable government to deliver proper services to the citizens of the country. This has encouraged the researcher to undertake the study in order to add more knowledge on the asset management process of the government, looking at the challenges and possible solutions. The need for this study was considered relevant and necessary as government departments and other private sectors face numerous challenges in implementing the asset management. Limpopo Department of Economic Development, Environment and Tourism, as a case study, faces challenges in fulfilling some of its mandate due to lack of support from asset management activities. In terms of its strategic plan, the department seeks to address issues relating to economic growth, the promotion and development of tourism and using environmental management to guide and monitor sustainable development in the province. These challenges have negative implications on the delivery of services to the communities it serves. In this study, the researcher investigated the following: demographic profile of respondents, challenges facing asset management, the impact of asset management on service delivery and lastly the best practice on the implementation of asset management. Data were analysed into themes and revealed communication, training, interpretation of relevant prescripts, limited resources, proper allocation of resources and effective participation of relevant stakeholders as, amongst others, challenges to the process. The study concluded by providing recommendations to management of the Limpopo Department of Economic Development, Environment and Tourism on how to improve the asset management activities to achieve the strategic goals of the department. The recommendations proposed are improved communications with stakeholders, development of asset plan, skills capacity of asset management officials and sourcing the asset information system that integrates with the financial system to provide a reliable asset register.
Thesis (MBA.) -- University of Limpopo, 2015
Keywords: Local economic development; Small business development; Economic growth; Limpopo Department of Economic Development Environment and Toursim; Asset management; Asset allocation; Government property -- Management